Предмет: Алгебра,
автор: Zhaina111
cos2a/1-sin2a=1+sin2a/cos2a
Ответы
Автор ответа:
0
cos2a/(1-sin2a)=(cosa²-sin²a)/(cos²a+sin²a-2sinacosa)=
=(cosa-sina)(cosa+sina)/(cosa-sina)²=(cosa+sina)/(cosa-sina)
(1+sin2a)/cos2a=(cos²a+sin²a+2sinacosa)/(cosa-sina)(cosa+sina)=
=(cosa+sina)²/(cosa-sina)(cosa+sina)=(cosa+sina)/(cosa-sina)
(cosa+sina)/(cosa-sina)=(cosa+sina)/(cosa-sina)
=(cosa-sina)(cosa+sina)/(cosa-sina)²=(cosa+sina)/(cosa-sina)
(1+sin2a)/cos2a=(cos²a+sin²a+2sinacosa)/(cosa-sina)(cosa+sina)=
=(cosa+sina)²/(cosa-sina)(cosa+sina)=(cosa+sina)/(cosa-sina)
(cosa+sina)/(cosa-sina)=(cosa+sina)/(cosa-sina)
Похожие вопросы
Предмет: История,
автор: mslubas2007
Предмет: Обществознание,
автор: asanova1505
Предмет: Литература,
автор: annaaaa943
Предмет: Физика,
автор: NastyaNikonorova